Hepatitis C Virus Infection in Indigenous Populations in the United States and Canada. Issue 1 (29th November 2019) - Bruce, Veronica; Eldredge, Jonathan; Leyva, Yuridia; Mera, Jorge; English, Kevin; Page, Kimberly
Abstract: American Indian/Alaska Native (AI/AN) and Canadian Indigenous people are disproportionally affected by hepatitis C virus (HCV) infection yet are frequently underrepresented in epidemiologic studies and surveys often used to inform public health efforts. We performed a systematic review of published and unpublished literature and summarized our findings on HCV prevalence in these Indigenous populations. We found a disparity of epidemiologic literature of HCV prevalence among AI/AN in the United States and Indigenous people in Canada. The limited data available, which date from 1995, demonstrate a wide range of HCV prevalence in AI/AN (1.49%–67.60%) and Indigenous populations (2.28%–90.24%). The highest HCV prevalence in both countries was reported in studies that either included or specifically targeted people who inject drugs. Lower prevalence was reported in studies of general Indigenous populations, although in Canada, the lowest prevalence was up to 3-fold higher in Aboriginal people compared with general population estimates. The disparity of available data on HCV prevalence and need for consistent and enhanced HCV surveillance and reporting among Indigenous people are highlighted. HCV affects Indigenous peoples to a greater degree than the general population; thus we recommend tribal and community leaders be engaged in enhanced surveillance efforts and that funds benefitting all Indigenous persons be expanded to help prevent and cover health care expenses to help stop this epidemic.